A metodologia de projetos do programa A União Faz a Vida na educação física : possibilidades de uma prática pedagógica - Pondé, Gislaine Lisboa (2019)
The Projects Methodology of the Program “A União Faz a Vida” (Union Makes Life) – PUFV is a widespread practice in Nova Mutum, Mato Grosso, since 2005, and has been adhered by schools from all the networks as a possibility of pedagogical practice which values the cooperation and citizenship as fundamental attributes for the educational process. Regarding its proposal of a cooperative education, it is aimed at verifying the implications of the projects methodology of PUFV’s work in Physical Education classes in public schools in the urban area of Nova Mutum, Mato Grosso. Specifically, it is expected to identify teachers’ motivations and justifications to adhere to the projects methodology, as well as how they comprehend the meaning of this pedagogy in the process of professional intervention, and it consequences for students’ learning; identifying the managers’ perceptions as to the implementation of the projects methodology of PUFV in Physical Education in public schools in the urban area of Nova Mutum, Mato Grosso. As a form of pedagogical way which can meet the goals of this study, we did a qualitative approach research, described by Bogdan and Biklen (1994), descriptive, inductive, in public schools of the urban area of Nova Mutum that adhered to PUFV and also attend from second year of Elementary School, whose Physical Education classes are given by qualified teachers, who developed some project between 2016 and 2018. Five schools participated, being three municipal ones and two state ones. The professors’ board Is composed by nine professors, who were interviewed, as well as the managers who accompanied the development of the projects, in order to present their perceptions considering this pedagogical practice, subsiding the data analysis by the Content Analysis, proposed by Bardin (2011), in which the register units are defined and organized in context units, being organized and classified according to their characteristics in terms of homogeneity by the procedure called “collection”, which results from the categories elaborated after the organization of the content expressed in the interviews. Among the results, we highlight on the purpose of the PUFV, a methodological way focused on protagonism and the participation of the students in the development of projects, as well as in an interdisciplinary relationship still fragile, however, it is in progress. We highlight by using charts and info graphs the importance of the educational value of PUFV. However, the effectiveness in terms of the number of projects presents itself in a discrete way in Physical Education classes.